2019
DOI: 10.1177/2040622319862691
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucagon-like peptide 1 receptor agonists on comorbidities in older patients with diabetes mellitus

Abstract: Elderly patients with diabetes are at high risk of polypharmacy because of multiple coexisting diseases and syndromes. Polypharmacy increases the risk of drug–drug and drug–disease interactions in these patients, who may already have age-related sensory and cognitive deficits; such deficits may delay timely communication of early symptoms of adverse drug events. Several glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have been approved for diabetes: liraglutide, exenatide, lixisenatide, dulagluatide, sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 118 publications
(255 reference statements)
0
28
0
Order By: Relevance
“…In addition to glycemic and metabolic benefits, liraglutide is well known for gastrointestinal side effects including nausea, vomiting, and diarrhea [ 20 ]. Most (48%) of the patients in our study also reported nausea.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to glycemic and metabolic benefits, liraglutide is well known for gastrointestinal side effects including nausea, vomiting, and diarrhea [ 20 ]. Most (48%) of the patients in our study also reported nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Also, older patients experienced more hypoglycemic episodes compared to younger patients, which is consistent with observations in a dulaglutide-treated Japanese patient population [ 9 ] and with lixisenatide [ 19 ]. This could be because generally in older patients with T2D aged > 60 years, hypoglycemia is a frequently observed adverse event [ 20 ]. Furthermore, we observed a higher incidence of hypoglycemia in patients taking concomitant SU either as monotherapy or in combination with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 binds to GLP-1R in beta-cells of the pancreas to increase insulin secretion and reduce glucagon synthesis. GLP-1R agonists have been shown to reduce hyperlipidaemia, hypertension and fatty liver in diabetic patients [ 29 ]. GLP-1R agonists exenatide, liraglutide and taspoglutide are able to modestly decrease low-density lipoprotein-cholesterol, triglycerides and total cholesterol [ 30 ].…”
Section: Gut Microbiota Metabolites In the Pathogenesis Of Nafldmentioning
confidence: 99%